Tsukamoto Fuzzy Method Analysis in Laptop Damage Diagnosis - Yonata Laia; Agusman Halim (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
As we know now that laptop and PC users are increasing, but the system for detecting damage that is definitely still minimal, this panel will try to solve the problem. Based on the results of the problems that have been described in the background of this research, namely the uncertainty of each technician to determine the damage that occurs on the laptop, this research creates an expert system with the Tsukamoto fuzzy method in diagnosing laptop dredging based on the symptoms experienced by consumers. In accordance with the results of testing the symptom and damage data that has been tested on this system, the data as in the table above in the third sequence is inputting symptoms G030, G037, G034 then the damage will occur with K003. This system also managed to show the results of the research that the level of truth was only at 85%. This system can also be used for anyone who needs it.